Anatomage - the virtual dissection tool and its uses: A narrative review - Raja, BS; Chandra, A; Azam, MQ; Das, S; Agarwal, A (Journal of postgraduate medicine, 2022)
Advancement in technology has given students and institutes an educational, interactive, and diagnostic aid with virtual reality functionality known as the Anatomage table. This review analyses the various spheres of the medical field where the 3D virtual tool is being used and assesses its acceptability, convenience, and practical application. A search for relevant studies in various databases namely Pubmed, Embase, Wiley Library, and Google Scholar was performed, and the data was compiled to understand the use of the Anatomage table. The search yielded a total of 24 studies that focused on the use of the Anatomage table. Eleven articles focused on using Anatomage as a learning tool and 13 described the perception of the Table. Anatomage table offers an excellent tool for learning anatomy by virtual dissection. The tool is not only used as a teaching aid, but also as a diagnostic and planning tool in residency programs. Adding the tool as an educational aid boosts the existing curriculum and helps to counter the challenges with cadaveric dissection. The equipment cost and its maintenance charges may be a deciding factor for the underutilization of the tool in developing countries.